Liability Annex to the Protocol on Environmental Protection to the Antarctic Treaty - Proelss, Alexander; Steenkamp, Robert C. (Springer International Publishing, 2022)
Abstract Twenty-nine States (the ‘Consultative Parties’), each with a substantial interest in Antarctica, collectively manage Antarctica through a system of consensus-based decisions. Traditionally, the Antarctic Treaty together with recommendations and measures adopted by the Antarctic Treaty Consultative Meetings (ATCM), the Convention on the Conservation of Antarctic Marine Living Resources (CAMLR Convention) and the Convention for the Conservation of Antarctic Seals (CCAS) form the basis of the Antarctic Treaty System. However, the Consultative Parties began to expand their environmental responsibilities in Antarctica in 1970 and agreed that they “should assume responsibility for the protection of the environment and the wise use of the Treaty area”. A major step in this regard was the addition to the Antarctic Treaty System of the Protocol on Environmental Protection to the Antarctic Treaty (PEPAT or the Protocol). Together with safeguarding free and peaceful scientific research, the Protocol incorporates the protection of the Antarctic environment into the Antarctic Treaty System. The Protocol has six annexes, with Annex VI (Liabilities Arising from Environmental Emergencies) being a product of the obligations contained in Articles 15 and 16 of the PEPAT. Specifically, Article 16 of the PEPAT states that: